Pengaruh Terpaan Informasi Prostitusi Seungri Eks Big Bang di Media Sosial Twitter terhadap Sikap Followers @SeungriID - Permana Putri, Khairunnisa Devani Aqtus (UI Scholars Hub, 2020)
This research aims to determine the effect of information exposure about prostitution by the former of Big Bang, Seungri on Social Media Twitter, toward followers @SeungriID. Lots of pros and cons for fans of this information. Twitter is the main driving media for the Korean Wave. The information on Twitter forming a person's attitude. This research is a quantitative study using data obtained from distributing questionnaires to followers of @SeungriID and using linear regression analysis. The variables are information exposure on social media with dimensions of frequency, duration and attention and attitude variables which have cognitive, affective and conative dimensions. The sampling technique used nonprobabiliy sampling technique by taking a sample of 100 respondents from 7,881 followers. From the research that has been done, there is an effect between information exposure about prostitution by the former of Big Bang's Seungri on social media Twitter on the attitudes of followers @SeungriID with a weak correlation level. This is due to the lack of frequency and duration of respondents reading information about the prostitution of the former Big Bang's Seungri, which on average only takes research, to obtain data in the form of factors that affect attitudes towards in-depth information.